2006
DOI: 10.1002/cncr.21755
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiologic predictors of invasive pulmonary aspergillosis in cancer patients

Abstract: BACKGROUNDInvasive pulmonary aspergillosis (IPA) is a life‐threatening infection in immunocompromised patients. The outcome of such infections depends on early diagnosis and prompt initiation of therapy. The objective of the current study was to determine the significant predictive factors that characterize IPA in patients with cancer.METHODSThe clinical characteristics and computed tomography (CT) findings for 47 cases with IPA were retrospectively reviewed and compared with 49 controls (patients diagnosed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Therefore, determination of the correct risk level forms the basis of AFP. Furthermore, besides an increase in mortality, IFDs lead to delays in scheduled treatments (chemotherapy, stem cell transplantation), longer hospital stays, and increased treatment costs [ 10 , 11 , 12 , 13 ].…”
Section: Determination Of Risk and Targets Of Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, determination of the correct risk level forms the basis of AFP. Furthermore, besides an increase in mortality, IFDs lead to delays in scheduled treatments (chemotherapy, stem cell transplantation), longer hospital stays, and increased treatment costs [ 10 , 11 , 12 , 13 ].…”
Section: Determination Of Risk and Targets Of Prophylaxismentioning
confidence: 99%
“…For instance, the use of new monoclonal antibodies may alter the risk profile of chronic lymphocytic leukemia patients who are considered to be at low risk [ 18 ]. Similarly, use of new protocols in both the preparative regimen and GVHD prophylaxis in allogeneic stem cell transplantation, different stem cell sources (bone marrow, peripheral blood, umbilical cord blood), donor type (unrelated donors, relatives with perfect or partial match), stem cell manipulation (T-cell reduction), and superimposed infections (cytomegalovirus, respiratory syncytial virus infections) may lead to remarkable changes in the risk profile [ 10 , 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Determination Of Risk and Targets Of Prophylaxismentioning
confidence: 99%
“…The sensitivity of Aspergillus galactomannan (GM) enzyme immunoassay testing is 82% (ranges from 73 to 90%) and its specificity is 81% (ranges from 72 to 90%) in the immunocompromised population who are not receiving anti-mold therapy or prophylaxis [ 6 , 7 ]. In addition, specific radiological findings detected on high-resolution computed tomographic (CT) scans highly correlated with the presence of fungal infection [ 8 , 9 ]. These advances in diagnostic techniques, may help the clinician to establish an early diagnosis and rapidly initiate a diagnostic driven treatment instead of the current empiric approach that may lead to unnecessary treatment to certain patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advances in antifungal therapy and prophylaxis in the past decade (1, 7, 13–16), IFI remains a major threat for the survival of SCT recipients. Moreover, it is still difficult to establish the diagnosis of IFI, particularly in the early phase of transplantation and for patients in critical status (5, 17). Studies by Martino et al (11) showed that risk stratification by risk factors of IFI can identify patients with high risk of IFI.…”
mentioning
confidence: 99%